Effect of β-hydroxybutyrate on behavioral alterations, molecular and morphological changes in CNS of multiple sclerosis mouse model - Sun, Wei; Wen, Min; Liu, Min; Wang, Qingpeng; Liu, Quiqin; Li, Lanjie; Siebert, Hans-Christian; Loers, Gabriele; Zhang, Ruiyan; Zhang, Ning (Frontiers in Aging Neuroscience, 2022)
Multiple sclerosis (MS) is a chronic inflammatory and degenerative disease of CNS. Aging is the most significant risk factor for the progression of MS. Dietary modulation (such as ketogenic diet) and caloric restriction, can increase ketone bodies, especially β-hydroxybutyrate (BHB). Increased BHB has been reported to prevent or improve age-related disease. The present studies were performed to understand the therapeutic effect and potential mechanisms of exogenous BHB in CPZ-induced demyelinating model. The results showed that BHB treatment prevented myelin loss, decreased the activation of astrocyte as well as microglia, and up-regulated the neurotrophin brain-derived neurotrophic factor in both the corpus callosum and hippocampus. Meanwhile, BHB treatment increased the number of MCT1+ cells and APC+ oligodendrocytes. Furthermore, the treatment decreased the expression of HDAC3, PARP1, AIF and TRPA1 which is related to oligodendrocyte (OL) apoptosis in the corpus callosum, accompanied by increased expression of TrkB. This leads to an increased density of doublecortin (DCX)+ neuronal precursor cells and mature NeuN+ neuronal cells in the hippocampus. As a result, BHB treatment effectively promotes the generation of PDGF-Ra+ (oligodendrocyte precursor cells, OPCs), Sox2+ cells and GFAP+ (astrocytes), and decreased the production of GFAP+ TRAP1+ cells, and Oligo2+ TRAP1+ cells in the corpus callosum of mouse brain. Thus, our results demonstrate that BHB treatment efficiently supports OPC differentiation and decreases the OLs apoptosis in CPZ-intoxicated mice, partly by down-regulating the expression of TRPA1 and PARP, which is associated with the inhibition of the p38-MAPK/JNK/JUN pathway and the activation of ERK1/2, PI3K/AKT/mTOR signaling, supporting BHB treatment adjunctive nutritional therapy for the treatment of chronic demyelinating diseases, such as multiple sclerosis (MS).